Disquisition of Drug Dose Determinations to Effectuate Sustained Therapeutic Response in Patients: A Comprehensive Review - Chandrasekar, Pooja; Joji, Mariyam Susan; Ramesh, Sashtipriyaa; Moorthy, Jagadeesan (Journal of Pharmacy Practice and Community Medicine, 2026)
According to the World Health Organisation, the Defined Daily Dose is the estimated daily maintenance dosage for a medication used for its primary indication in humans. Drug dose determination is extremely important for any drug. When a newly created, more precise dose plan differs considerably from the authorised label, it is crucial to assess the stage of proof needed to modify the label and clinical practice. Age has a significant influence on dose modification, as the acronym implies, because different age groups have different pharmacokinetic and pharmacodynamic characteristics. Furthermore, the measuring of body surface area is one of the most used methods for determining the dosage of chemotherapy medications. The clinical practice guidelines frequently base their recommended dosages on research that include both acute and severe cases of a particular ailment. For drugs acting on central nervous system, tapering of the dose is necessary. Starting such treatment at a low dose and gradually increasing it may reduce the likelihood of the side effects. This all-encompassing strategy emphasizes the value of customized medicine in contemporary clinical practice while promoting patient-centered care. This review article schemes about the various drug dosing considerations reliant on the demographic data, severity of the disease, as well as the individual patient response considering the resulting pharmacokinetics and pharmacodynamics.
Keywords: Drug Dosing; Medication Management; Pharmacodynamics; Pharmacokinetics; Therapeutic Index